2019
DOI: 10.1002/pld3.164
|View full text |Cite
|
Sign up to set email alerts
|

The rhg1‐a (Rhg1 low‐copy) nematode resistance source harbors a copia‐family retrotransposon within the Rhg1‐encoded α‐SNAP gene

Abstract: Soybean growers widely use the R esistance to H eterodera g lycines 1 ( Rhg1 ) locus to reduce yield losses caused by soybean cyst nematode (SCN). Rhg1 is a tandemly repeated four gene block. Two classes of SCN resistance‐conferring Rhg1 haplotypes are recognized: rhg1‐a (“Peking‐type,” low‐copy number, three or fewer Rhg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 81 publications
1
33
0
Order By: Relevance
“…TEs regulating defense or susceptibility genes also have been reported ( Tsuchiya and Eulgem, 2013 ; Berg et al, 2015 ). An intact copia retrotransposon ( RAC ) was found within intron 1, anti-sense to H. glycines resistance gene rhg1-a α-SNAP open reading frame, and RAC has intrinsic promoter activities in soybean ( Bayless et al, 2019 ). Hu et al (2019) identified the unevenly distributed presence/absence variants of gene structure across the genome between TM-1 and Hai7124 to be mostly copia elements (LTR type) that were found in coding DNA sequence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TEs regulating defense or susceptibility genes also have been reported ( Tsuchiya and Eulgem, 2013 ; Berg et al, 2015 ). An intact copia retrotransposon ( RAC ) was found within intron 1, anti-sense to H. glycines resistance gene rhg1-a α-SNAP open reading frame, and RAC has intrinsic promoter activities in soybean ( Bayless et al, 2019 ). Hu et al (2019) identified the unevenly distributed presence/absence variants of gene structure across the genome between TM-1 and Hai7124 to be mostly copia elements (LTR type) that were found in coding DNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…The enzyme serine hydroxymethyltransferase (SHMT) encoded by Rhg4 is associated with the resistance ( Liu et al, 2012 ), and copy number of rhg1 determines soybean resistance or susceptibility ( Cook et al, 2012 , 2014 ). Recently, Bayless et al (2019) found a copia family retrotransposon was harbored within the Rhg1 -encoded α-SNAP (alpha-soluble NSF attachment protein) gene in the rhg1-a ( Rhg1 low-copy) nematode resistance source.…”
Section: Introductionmentioning
confidence: 99%
“…Three genes located in the 31-kilobase segment are required for resistance, which encode for an amino acid transporter, an alpha-soluble NSF (N-ethylmaleimide–sensitive factor) attachment protein (α-SNAP) protein and a wound-inducible domain (WI12) protein ( Cook et al, 2012 ; Guo et al, 2019 ). The rhg1-a and rhg1-b haplotypes encode two different α-SNAP variants ( Liu et al, 2017 ; Bayless et al, 2019 ), but both variants hyperaccumulate at SCN infection sites ( Bayless et al, 2016 , 2019 ; Lakhssassi et al, 2020a ). The rhg1-a encoded α-SNAP carries a copia retrotransposon in its structure named RAC ( Rhg1 α-SNAP copia), which harbors intrinsic transcriptional activity ( Bayless et al, 2019 ).…”
Section: Quantitative Trait Loci Conferring Host-specific Resistance mentioning
confidence: 99%
“…TEs regulating defense or susceptibility genes also have been reported (Tsuchiya and Eulgem, 2013;Berg et al, 2015). An intact copia retrotransposon (RAC) was found within intron 1, anti-sense to H. glycines resistance gene rhg1-a α-SNAP open reading frame, and RAC has intrinsic promoter activities in soybean (Bayless et al, 2019). Hu et al (2019) identified the unevenly distributed presence/absence variants of gene structure across the genome between TM-1 and Hai7124 to be mostly copia elements (LTR type) that were found in coding DNA sequence.…”
Section: Discussionmentioning
confidence: 99%